Endometriosis, infertility and occupational life: women's plea for recognition - Letizia Gremillet; Antoine Netter; Irène Sari-Minodier; Laura Miquel; Arnaud Lacan; Blandine Courbiere (BMC, 2023)
Abstract The objective of this study was to explore and describe the specificities of the occupational life of infertile endometriotic women treated by in vitro fertilization. We conducted a qualitative monocentric study between December 2020 and June 2021. Twelve semi-structured in-depth interviews using a theme-based interview guide with open questions were undertaken with infertile women with deep infiltrating endometriosis. Data analysis was conducted using an inductive approach according to the grounded theory method. Three main themes emerged from the interviews: (i) barriers to reconciling illness and work life, (ii) facilitating factors for well-being at work, and (iii) consequences and outlooks. It appeared that the time of infertility treatment represents a particular period of change in the working lives of women with endometriosis. For most women, these changes are experienced negatively, often with a renunciation of goals. For others, this is the time to communicate the difficulties linked to their illness to their professional entourage. There is a long path ahead to finally achieving recognition of endometriosis in the context of professional life.